Modern approaches to global and governmental regulation of virtual assets: what to choose to support digital innovations? - Kud, Aleksandr (Pressing Problems of Public Administration, 2023)
The paper offers a critical outlook at modern approaches to supranational and governmental regulation of the circulation of virtual assets, which have already developed with confidence and which actually determine the conflict between generally global and national views on a very heterogeneous category – virtual assets. The purpose of this article is to summarize some key regulatory approaches spread globally – from global to state levels – regarding the circulation of virtual assets and their critical analysis from the point of view of supporting digital innovation in a national economy. The paper is a continuation of the ongoing wide-ranging expert and political debate about what government officials and presidents should be guided by in matters of circulation of virtual and, in particular, backed (secured) tokenized assets. The logic of the presentation and judgments in the paper is related to the step-by-step consideration of such issues: (1) the basic political approach of the International Monetary Fund and its discussion from a public-management point of view; (2) institutional and administrative risks for governments regarding the full implementation of the IMF’s 2023 policy recommendations on the regulation of virtual assets; (3) widespread standards for the prudent (prudential) circulation of virtual assets, which were developed by other authoritative supranational organizations; (4) an overview of key problems in the coordination of multi- and single-level approaches to the regulation of virtual assets; (5) highlighting 5 regulatory approaches in the ways and scope of governmental (national) regulation of virtual assets currently operating in the world; (6) author’s comparison and assessment of regulatory approaches; (7) assessment of Ukrainian prospects in supporting technological innovations in the field of circulation of virtual assets in the context of the adoption of the new law «On Virtual Assets» in 2023. The author makes the final conclusion that, generally, modern regulatory efforts of supranational and state regulators in the field of circulation of virtual assets are mostly focused on the problems of illegal financing, unfair competition and the integrity of new and old markets of financial assets, as well as focused on requirements for experience and financial stability of private service providers in the field of virtual assets. However, there is a growing understanding that regulators will arrive at a more or less single or multiple regulatory approach, which will be set at the supranational level, and this will only facilitate technological innovation. Such an approach will most likely be combined – based on regulatory flexibility and on the basis of principles (expected results).